Port service quality in the supply chain management context - Cheng, Ying Ying. (2012)
Purpose - The purpose of this paper is to widen knowledge on port service quality in the context of supply chains and by proposing and testing a new service quality model, identify the key determinants of a quality port. The benefits of port service quality, impact of port service quality on supply chain performance and the critical factors for successful implementation of port service quality will also be examined from the perspective of port users.